2021
DOI: 10.3389/fphar.2021.678611
|View full text |Cite
|
Sign up to set email alerts
|

Development of Synergy-Based Combination for Learning and Memory Using in vitro, in vivo and TLC-MS-Bioautographic Studies

Abstract: The present study is aimed at developing a synergistic combination to enhance learning and memory in Alzheimer’s patients with the help of eight common medicinal plants used in the AYUSH system. Aqueous and hydroalcoholic extracts of eight medicinal plants from the AYUSH system of medicine were prepared. These were subjected to in vitro anticholinesterase activity, to find out the combination index of synergistic combination. The synergistic combination and their individual extracts were subjected to total phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In a related investigation, Withania somnifera lowered AChE activity by 30% when used at a concentration of 12.50 µg/mL, and reached roughly 50% inhibition at 50 µg/mL [36]. A previous study in oral treatment of ZnONPS and ZnCAP for brain abnormalities caused by retinone RTNE has significantly higher inhibition activity of AChE [37].…”
Section: Acetylcholinesterase (Ache) Inhibitory Activitymentioning
confidence: 83%
“…In a related investigation, Withania somnifera lowered AChE activity by 30% when used at a concentration of 12.50 µg/mL, and reached roughly 50% inhibition at 50 µg/mL [36]. A previous study in oral treatment of ZnONPS and ZnCAP for brain abnormalities caused by retinone RTNE has significantly higher inhibition activity of AChE [37].…”
Section: Acetylcholinesterase (Ache) Inhibitory Activitymentioning
confidence: 83%
“…This finding is in agreement with the report of Maya and Sarada [ 87 ] who suggested important AChE inhibitory activity of methanolic extracts of roots, despite its low content of polyphenols. Apart from single-extract treatments, Khan et al [ 88 ] recently suggested the synergistic effects of the aqueous extracts of W. somnifera and Myristica fragrans which significantly increased the IC 50 values in in vitro anticholinesterase assays, compared to treatments with single extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Quercetin, as a component of Epimedium, has been shown to reduce oxidative stress, decrease NO levels, and inhibit NOS activity in brain tissue. It exerted a protective role on cognitive function in VaD by improving cerebral blood flow, regulating oxidative stress, cerebral energy metabolism and cholinergic function (Tota et al, 2010 ; Khan et al, 2021 ; Singh and Garabadu, 2021 ). Researches also have found that luteolin, another component of Epimedium, can inhibit cerebral ROS levels, and modulate inflammatory factors to achieve protective effects on neurons through anti-oxidative stress, anti-inflammatory and anti-apoptotic effects (Bastianetto et al, 2011 ; Wang and Gao, 2015 ).…”
Section: Discussionmentioning
confidence: 99%